Les infirmières-visiteuses pendant l’entre-deux-guerres en Haute-Normandie : entre professionnalisme officiel et bénévolat officieux - Stéphane Henry (Genre & Histoire)
The evolutions of the status of the visiting nurse echo the evolution in women's position within the workforce: marginal prior to 1914, revealed during the First World War, idolized or disparaged in the inter-war years. Despite legislation governing this new corps of women nurses in the early twenties, examples from the departments of the Seine-Inférieure and  the Eure make clear that it retained many attributes of volunteer work. Moreover, although the leaders of the war against tuberculosis, such as Albert Calmette, regularly praised the profession, they nonetheless sought to regulate it strictly, fearing a move toward excessive autonomy. The article considers the nature of this relative professionalization as well as the particularly difficult working conditions of these novice women professionals, who were ultimately ill-equipped to handle the misery they encountered.  Thus, while the emergence of the visiting nurse represented a major shift in the acceptance of women’s skilled work in French society, the ability of these women to exert their skills effectively in the context of struggles against social scourges (tuberculosis and infant mortality) was limited in practice.